The medieval roots of antisemitism in Sweden: Old Swedish and Latin manuscript traditions - Heß, Cordelia (Nordisk judaistik/Scandinavian Jewish Studies, 2023)
The lack of a local Jewish community did not prevent medieval Swedish clerics and lay people from being interested in Jews and Jewish questions. They bought, translated, read and preached from most of the available textual sources and thus spread the widely available views of the hermeneutical Jew: a cruel, stubborn and ugly person and at the same time a cipher for the entire Jewish people both in biblical times and today. This article gives an overview of the Latin and vernacular manuscripts with anti-Jewish motifs and texts and shows that the main and most common textual models and motifs were available in Swedish libraries and collections, from legends via apocryphal texts to fake disputations – adding up to a relatively complete ‘hermeneutical Jew’. A focus was, as in the rest of Europe, on Passion-related piety, which was the most common form of piety in the late Middle Ages – and usually connected with distinct anti-Jewish features. The fact that we can establish direct and indirect textual and narrative lines of tradition between the medieval codices and modern printed booklets of the nineteenth century proves the long-lasting intelligibility of anti-Jewish stereotypes in Sweden – developed and spread completely independently from the Jewish minority. The medieval perspective thus adds a much-needed nuance to the debate about antisemitism in the North: it did not need any actual Jews; it simply made up its own, based on the general Christian tradition.